Osteoarthritis in Italy: Impact on Health-Related Quality of Life and Health Care Resources - Berto, Patrizia; Sanna, Maria Domenica; Jackson, James; Berry, Mia; Jackson, Jessica (Farmeconomia. Health Economics and Therapeutic Pathways, 2021)
OBJECTIVE: To determine how osteoarthritis (OA) severity correlates with self-reported outcomes relevant from the patient’s perspective in the Italian clinical setting.METHODS: Data were drawn from the 2017-18 Adelphi OA Disease Specific ProgrammeTM (DSP). Data were collected in the Italian clinical practice settings by primary care physicians, rheumatologists, orthopedists, and their patients with OA, during their regular office visits. Physicians completed information about OA-related visits to healthcare professionals (HCPs), tests/scans conducted, emergency room (ER) visits, surgeries, and OA-related treatment. Physicians also rated patients’ functioning on a 0 to 10 scale (0 = fully functional; 10 = completely impaired). Outcomes included Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score, functional limitations, treatment needs, EuroQoL-5 Dimension (EQ-5D) visual analogue scale (VAS), the work productivity and activity impairment. Descriptive statistics (numbers and percent for categorical variables; means with standard deviations [SD] for continuous variables) were used to evaluate the different variables as appropriate.RESULTS: The study population comprised 900 patients from Italy with knee (40.9%), back (38.7%), hip (27.9%), and/or shoulder (20.3%) OA. Mean age was 66.6 years with a prevalence of female (63%) patients. Patients had mild (26%), moderate (54%), severe (20%) disease severity. Patients with severe disease reported higher functional limitations, greater use of treatments, reduced quality of life, and impaired work productivity and activity. The burdens were higher among elderly and obese patients and in patients with highest pain severity score.CONCLUSIONS: The results from this cross-sectional study show the impact of OA disease severity on all dimensions of health-related quality of life (HRQoL), as well as in OA-related health care resource use.